Adjuvant chemotherapy is associated with an overall survival benefit regardless of age in ER+/HER2- breast cancer pts with 1-3 positive nodes and oncotype DX recurrence score 20 to 25: an NCDB analysis - Stabellini, Nickolas; Cao, Lifen; Towe, Christopher W.; Luo, Xun; Amin, Amanda L.; Montero, Alberto J. (Frontiers in Oncology, 2023)
Background: The RxPONDER trial found that among breast cancer patients with estrogen receptor positive (ER+) breast cancer, 1-3 positive axillary nodes, and a recurrence score of <25, only pre-menopausal women benefitted from adjuvant chemoendocrine therapy; postmenopausal women with similar characteristic did not benefit from adjuvant chemotherapy. We aimed to replicate the RxPonder trial using a larger patient cohort with real world data to determine whether a RS threshold existed where adjuvant chemotherapy was beneficial regardless of age. Methods: The National Cancer Database (NCDB) was queried for women with ER+, human epidermal growth factor receptor 2 (HER2) negative breast cancer, 1-3 positive axillary nodes, and RS <25 who received endocrine (ET) only or chemo-endocrine therapy (CET). Cox regression interaction was explored between CET and age as a surrogate for menopausal status. Results: The final analytic cohort included 28,427 eligible women: 7,487 (26.3%) received adjuvant CET and 20,940 (73.7%) ET. In the entire cohort, RS had a normal distribution, with a median score of 14. After correcting for demographic and clinical variables, a threshold effect was observed with RS >20 being associated with a significantly inferior overall survival (OS) (P value range: < 0.001-0.019). In women with RS of 20-25, CET was associated with a significant improvement in OS compared to ET alone, regardless of age (age <=50: HR = 0.334, P=0.002; age>50: HR=0.521, P=0.019). Conclusions: Among women with ER+/HER2- breast cancer with 1–3 positive nodes, and a RS of 20-25—in contrast to the RxPONDER trial—we observed that CET was associated with an OS benefit in women regardless of age.